2022
DOI: 10.1111/andr.13264
|View full text |Cite
|
Sign up to set email alerts
|

Thermal male contraception: A study of users’ motivation, experience, and satisfaction

Abstract: Purpose:The aim of this study is to evaluate the motivations, experience, and acceptability of thermal male contraception (TMC) in male partners of couples requesting the use of TMC as the only couple contraceptive. Materials and methods:To the 72 men of couples seeking male contraception and using TMC between 2011 and 2019, we suggested an anonymous online survey (93 questions) exploring population characteristics, contraceptive histories, motivations for choosing TMC, patient experience at the successive pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Table 2). For the purposes of this review, only male contraceptives with a demonstrated pharmacological mechanism are discussed in detail, although thermal and vas-occlusive methods of reversible male contraception are in development and rely on thermal dysregulation of spermatogenesis, and obstructive, dissolvable, or degradable implants, respectively ( Lohiya et al, 2001 ; Soufir, 2017 ; Khourdaji et al, 2018 ; Long et al, 2021 ; Joubert et al, 2022 ).…”
Section: Novel Methods Currently In Developmentmentioning
confidence: 99%
“…Table 2). For the purposes of this review, only male contraceptives with a demonstrated pharmacological mechanism are discussed in detail, although thermal and vas-occlusive methods of reversible male contraception are in development and rely on thermal dysregulation of spermatogenesis, and obstructive, dissolvable, or degradable implants, respectively ( Lohiya et al, 2001 ; Soufir, 2017 ; Khourdaji et al, 2018 ; Long et al, 2021 ; Joubert et al, 2022 ).…”
Section: Novel Methods Currently In Developmentmentioning
confidence: 99%
“…66,67 Importantly, thermal male contraception appears to be reasonably well tolerated, with most men who use this method reporting that they would recommend it to others. 68 However, this method has not been approved for widespread use and has not been adopted by large numbers of men.…”
Section: Thermal Male Contraceptionmentioning
confidence: 99%